The Impact of Using Metaverse Technology in the Learning Process in Junior High Schools - Usfandi Haryaka; Warman (LPPM Undiksha, 2024)
In today's world of education, educational technology is integrated with Metaverse. However, in reality, there are still many schools that have not utilized Metaverse in the learning process. In theory, with the help of Metaverse, it can increase interest in learning. However, in reality, student learning outcomes in mathematics, science and social studies, science and social studies subjects obtained by students are actually low. This urgently needs to be studied with the gap between theory and facts in the field, with the aim of analyzing the extent to which Metaverse technology is used in the learning process in the classroom, especially in the learning process of mathematics, science and social studies, science and social studies in junior high schools. The research method used is quantitative using a questionnaire survey. The research sample was 360 teachers spread across Samarinda. The sample selection was carried out randomly to teachers who had used Metaverse as a tool in the learning process. Data collection techniques with questionnaires. Assessment scale from point 1 to point 5. Analysis techniques with descriptive statistics assisted by SPSS Version 25.0 by calculating the mean, percentage, standard deviation and standard deviation. As a result, teachers proved to be proficient in using Metaverse technology in teaching mathematics, science and social studies, science and social studies. It was found that Metaverse technology has been effectively integrated into teachers' teaching methods and teachers provide better learning experiences to students. The conclusion is that there is a significant difference between teachers' attitudes regarding the level of use of Metaverse technology. However, no significant difference was observed based on teachers' experiences in learning.